PROJECT BASED LEARNING DAN PEMBENTUKAN KARAKTER KERJA SAMA SISWA: STUDI KUALITATIF - Nuudiya Anburika; May Nanda Dwi Saharani; Faizatul Hasanah; Mujtahidin (STKIP Subang, 2026)
This study aims to describe the roles of students and teachers in building collaboration in Project Based Learning at Muhammadiyah 1 Elementary School, Bangkalan. This study uses a qualitative approach with descriptive methods. The research subjects consisted of fourth-grade teachers, sixth-grade teachers, and students at Muhammadiyah 1 Elementary School, Bangkalan. Data collection techniques were carried out through in-depth interviews and documentation of student project results. Data were analyzed descriptively to describe the roles of students, teachers, obstacles, and solutions in building collaboration through project-based learning. The results show that students' roles are seen through their involvement in group discussions, task distribution, information seeking, and collaborative project completion. Meanwhile, teachers act as learning designers, group builders, facilitators, mentors, and evaluators during project activities. However, student collaboration has not run optimally because several obstacles are still encountered, such as students dominating the group, passive students, conflicts between members, limited digital facilities, lack of structured learning tools, and limited learning time. This study concludes that the success of building collaboration in Project Based Learning requires the active role of teachers in designing structured learning and the active role of students in participating equally so that collaborative learning objectives can be optimally achieved.